Detecting sleep apnoea syndrome in primary care with screening questionnaires and the Epworth sleepiness scale. Issue 2 (3rd May 2019) - Senaratna, Chamara V; Perret, Jennifer L; Lowe, Adrian; Bowatte, Gayan; Abramson, Michael J; Thompson, Bruce; Lodge, Caroline; Russell, Melissa; Hamilton, Garun S; Dharmage, Shyamali C
Abstract: Objective: To examine the utility of apnoea screening questionnaires, alone and in combination with the Epworth sleepiness scale (ESS), for detecting obstructive sleep apnoea (OSA) in primary care. Design, setting: Prospective validation study in an Australian general population cohort. Participants: 424 of 772 randomly invited Tasmanian Longitudinal Health Study, 6th decade follow‐up participants with OSA symptoms (mean age, 52.9 years; SD, 0.9 year) who completed OSA screening questionnaires and underwent type 4 sleep studies. Main outcome measures: Clinically relevant OSA, defined as moderate to severe OSA (15 or more oxygen desaturation events/hour), or mild OSA (5–14 events/hour) and excessive daytime sleepiness (ESS ≥ 8); diagnostic test properties of the Berlin (BQ), STOP‐Bang and OSA‐50 questionnaires, alone or combined with an ESS ≥ 8. Results: STOP‐Bang and OSA‐50 correctly identified most participants with clinically relevant OSA (sensitivity, 81% and 86% respectively), but with poor specificity (36% and 21% respectively); the specificity (59%) and sensitivity of the BQ (65%) were both low. When combined with the criterion ESS ≥ 8, the specificity of each questionnaire was high (94–96%), but sensitivity was low (36–51%). Sensitivity and specificity could be adjusted according to specific needs by varying the STOP‐Bang cut‐off score when combined with the ESS ≥ 8 criterion. Conclusions: For people likely to trigger OSA assessment in primary care, the STOP‐Bang, BQ, and OSA‐50 questionnaires, combined with the ESS, can be used to rule in, but not to rule out clinically relevant OSA. Combined use of the STOP‐Bang with different cut‐off scores and the ESS facilitates a flexible balance between sensitivity and specificity.